Diseño de una propuesta de un sistema de trazabilidad de productos en la empresa super carnes karmel en barranquilla/atlántico (2022)
In this work the problem of the traceability system is solved. It has a brief introduction that explains why this work is done and a series of questions that will help define the objectives and develop the work.